Predicting missing items in shopping carts Machine Learning Approach - Indala Vinay Kumar Reddy,R.SenthilKumar (International Journal of Advanced Science and Technology, 2020)
In Existing exploration in association mining has concentrated essentially on the most proficient method to speed up the quest for regularly co-occurring gatherings of items in "shopping cart" sort of transactions. This paper adds to the last mentioned task by proposing a method that utilizes incomplete data about the substance of a shopping cart for the prediction of what else the client is probably going to purchase for example anticipating the missing items in shopping cart by computing the present transaction class and cross checking input items of the transactions with the precursors of the association rules created of that specific class. It additionally proposes things dependent on the offers accessible at that specific time dependent on the data of items of the present transactions. This paper likewise suggests a few items dependent on past transactions of a specific client for example client based prediction. The entire project is implemented by a basic UI where data sources, for example, client id, things alongside their amount is taken and predicts items dependent on produced association rules, offers accessible and furthermore clients past history.